Sustainable Resilience of Women Batik Makers in the Face of Environmental Degradation - Fubani, Amalia; Tumuyu, Sri Setiawati; Asteria, Donna (CV. Literasi Indonesia, 2025)
This study examines the impact of environmental degradation caused by urbanization and groundwater exploitation in North Pekalongan, which has triggered flooding, tidal inundation, and permanent waterlogging in 30% of the area. These conditions increase the vulnerability of female batik artisans in social, economic, and environmental aspects, threatening the sustainability of batik production. Using qualitative methods and an exploratory mixed approach, data were collected through in-depth interviews, surveys, and analyses such as overlay, indices, and SWOT. The findings show that: 1) Environmental degradation in Pekalongan City involves wetland conversion, land subsidence from soil deterioration and groundwater overuse, mangrove loss, and limited green spaces, all leading to flooding; 2) Female batik artisans face increased vulnerability and reduced resilience; 3) Stakeholders address these issues through government flood control measures, NGO sanitation projects, climate adaptation groups, and academic data support; 4) Sustainable resilience strategies prioritize offensive approaches, such as home elevation, empowering artisans, and leveraging external opportunities. The recommended sustainable resilience strategy is offensive, optimally leveraging internal strengths and external opportunities.